Sumber Penghasilan Masyarakat Nelayan (Studi Kasus di Desa Bungin Permai Kecamatan Tinanggea Kabupaten Konawe Selatan) - Luciana, Lulu; Hamzah, Awaluddin; Mardin, Mardin (Jurnal Ilmiah Membangun Desa dan Pertanian, 2017)
The aim of this research was to analyze the income source of the fisherman society. This research was conducted in Bungin Permai Village of Tinanggea Sub-district of Konawe Selatan District. The Sample was taken by purposive sampling methods. The number of samples in this research were 10 fishermen and the criteria of the informant fishermen were the catcher or the cultivation, it directly visible at the research social interaction, and they who can give the information although not directly involved in the social interaction that has been researched. The techniques of analysis that have been used at this research was the descriptive qualitative that was to Analysis showed that the main source of their income that they did every day, the unpredictable nature condition makes the fisherman can not fishing every day and it cause sometimes they did the diversification to fulfill their necessity or did the part-time job.